2020
DOI: 10.1186/s12872-020-01406-3
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-binding protein measurement improves the prediction of myocardial injury-related cardiogenic shock

Abstract: Background: Heparin-binding protein (HBP), a potent inducer of increased vascular permeability, is a potentially useful biomarker for predicting outcomes in patients with postoperative myocardial injury-related cardiogenic shock (MIRCS). We aimed to evaluate and validate HBP as a prognostic biomarker for postoperative MIRCS. Methods: We performed a case-control study in 792 patients undergoing cardiac surgery from January 1, 2016, to August 1, 2019, including 172 patients with postoperative MIRCS and 620 age-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The exclusion criteria were as follows: patients undergoing non-emergent surgery; deep hypothermic circulatory arrest (DHCA) was more than 25 minutes; poor hepatorenal dysfunction ( 19 ) (Child-Pugh Class B or C, estimated glomerular filtration rate <35 mL/min/1.73m 2 ); cardiogenic shock at the end of CPB ( 20 ) (vasoactive inotropic score>40, cardiac index <2.2L/min·m 2 , mean arterial pressure <65mmHg); fluid overload at the end of CPB ( 21 ) (inferior vena cava > 21mm); baseline inflammatory indicators abnormal ( 19 ) (interleukin-6 (IL-6) >10pg/mL, procalcitonin (PCT) >0.5 ng/mL, C reactive protein (CRP) >10 mg/L); diagnosed with inflammatory immune diseases, infectious or tumor disease; received treatment of sivelestat previously; had sivelestat allergy or intolerance; pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were as follows: patients undergoing non-emergent surgery; deep hypothermic circulatory arrest (DHCA) was more than 25 minutes; poor hepatorenal dysfunction ( 19 ) (Child-Pugh Class B or C, estimated glomerular filtration rate <35 mL/min/1.73m 2 ); cardiogenic shock at the end of CPB ( 20 ) (vasoactive inotropic score>40, cardiac index <2.2L/min·m 2 , mean arterial pressure <65mmHg); fluid overload at the end of CPB ( 21 ) (inferior vena cava > 21mm); baseline inflammatory indicators abnormal ( 19 ) (interleukin-6 (IL-6) >10pg/mL, procalcitonin (PCT) >0.5 ng/mL, C reactive protein (CRP) >10 mg/L); diagnosed with inflammatory immune diseases, infectious or tumor disease; received treatment of sivelestat previously; had sivelestat allergy or intolerance; pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent publication on 792 patients undergoing cardiac surgery with CPB, Pan et al showed that HBP predicted postoperative cardiogenic shock (16). Interestingly, in the study by Pan et al, mean HBP concentration was 91 ng/mL after 24 hours and 84 ng/mL after 48 hours also in cases not complicated by cardiogenic shock.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, two studies have described HBP levels in cardiac surgery. Pesonen et al showed a 39fold increase in HBP concentration during cardiac surgery with CPB and Pan et al demonstrated that elevated HBP levels after the release of cross-clamp predicted myocardial injury related cardiogenicshock after cardiac surgery (13,16). However, neither study did fully describe the intra-and postoperative dynamics of HBP or investigate whether the administration of heparin and protamine have any effect on HBP levels.…”
Section: Discussionmentioning
confidence: 99%
“…HBP is a highly positively charged molecule that has been shown to interact with negatively charged molecules and receptors, such as the glycocalyx of the endothelium. Therefore, we hypothesized that limited neutrophil activation occurs during the initial surgical trauma, which releases some HBP that binds to negatively charged molecules on the endothelial surface, such as proteoglycans (21). We used cultured endothelial cells to show that HBP adsorbs to the endothelial surface within 20 minutes and is then released within ve minutes of adding heparin.…”
Section: Discussionmentioning
confidence: 99%
“…Heparin itself has, in both in vitro and in vivo studies, been demonstrated to have bene cial effects in blocking HBP-induced vascular leakage and renal in ammation (21). Therefore, even if heparin induces an HBP elevation its effects are likely blocked by the presence high doses of heparin.…”
Section: Discussionmentioning
confidence: 99%